Pemetaan Satuan Lahan Zona Equifer yang Berada di Areal Patahan pada Sebagian Wilayah Desa Batumerah Kota Ambon - Edward Gland Tetelepta; Sri Widyanti; Mohammad Amin Lasaiba (Jurnal Pengabdian Arumbai, 2024)
This community service activity aims to map the land unit of aquifer zones in the fault area of Batumerah Village, Sirimau District, Ambon City, as a strategic step in groundwater resource management. Using geo-electromagnetic methods and Surfer 9.0 software, the activity successfully identified aquifer locations with an optimal depth of 50–80 meters. The collected data were analyzed and presented in the form of a Geographic Information System (GIS) to support integrated and sustainable water management planning. This activity involved village officials and the local community through education and data-based training to enhance their capacity to independently understand and manage water resources. The results showed that a technology-based approach combined with community participation is effective in providing solutions to groundwater availability challenges in fault areas. This activity is expected to serve as a foundation for better water resource management, with recommendations including continuous training, regular data updates, and community education on the importance of water conservation in the face of climate change.